Study on Performance of Walnut Shells Adsorbent in Nitrate Removal from the Aqueous Solutions - sayede samane taheri otaghsara; Mohammad Ali zazouli; Mohammad Ali Ebrahimzade; shahram eslami; yahya esfandiari (Mashhad University of Medical Sciences, 2019)
Background and purpose: High concentration of nitrate in drinking water can be detrimental to health. It can be reduced to nitrite in children Stomach and lead the methemoglobinemia. Therefore, the removal of nitrate from polluted water is necessary. The purpose of this study is to determine the effectiveness of walnut shell adsorbent in removing nitrates from aqueous solutions. Materials and methods: This experimental study was conducted in a batch laboratory scale. The walnut shell were collected and burned in the furnace at 700 סC in 1 hours and sieved in 20 -100 mesh. The optimum values of pH, contact time, adsorbent dosage and and the different concentrations of nitrate were experimented in lab scale conditions were determined. The nitrate concentration was measured in wavelength of 220 and 275 nm by spectrophotometer. Also pHpzc of absorbent have been evaluated. Results: The results showed that optimum pH was 9 so that by increasing and decreasing optimum pH, removal efficiency increase and decrease. The removal efficiency Increased until 120 minutes, but after 120 minutes the percentage of removal was reduced Increasing of adsorbent dosage and the different concentrations of nitrate cause the increase and decrease of adsorbtion respectively. At optimal conditions, nitrate removal efficiency was 78% Conclusion: The result of the present study shows that walnut shell can be used as an effective and cheap adsorbent for nitrate removal and the process is more efficient at Alkaline pH .